Task-Based Learning: Gaining Students’ Engagement to Improve Students’ Competence in Writing Procedure Text - Krismawarti Krismawarti; Arum Nisma Wulanjani (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
AbstractThis study aims to improve the quality of English learning at SMPN 2 Magelang. It focuses in improving the students’ writing competence of procedure text through task-based learning. The method used in this study was a classroom action research. There were two cycles carried in this study which included four stages in each cycle, they were planning, acting, observing, and reflecting. The data in this study were collected through observation, test, and also questionnaire. From the result, it was revealed that there was an improvement in the students’ writing competence of procedure text. Meanwhile, 92% of the students show a positive response towards the learning process.